“Those who need extra effort and who have not progressed”: Norwegian language teachers’ perceptions of multilingualism in school - Olaussen, Andrea Hjertås; Kjelaas, Irmelin (Målbryting, 2021)
This article presents four Norwegian language teachers’ perceptions of multilingualism in school. Linguistic diversity is emphasized in the new curriculum for the 10-year compulsory school in Norway (Kunnskapsløftet 2020), which makes it both important and interesting to investigate teachers, and especially language teachers, beliefs about multilingualism. The data consist of qualitative in-depth interviews, which are analyzed and discussed in light of theories about multilingualism and language ideology. The analysis demonstrates that the teachers have a narrow definition of multilingualism and multilingual students. Several associate multilingual students with students who have a different first language than Norwegian, who come from another country, who have low school progression and who lack Norwegian language skills. When it comes to the teachers’ didactic reflections about multilingualism in the classroom, the teachers are oriented towards Norwegian and the development of Norwegian language competence, and it is primarily cultural, not linguistic diversity that is highlighted as a resource in education. Based on these findings, we discuss how the teachers’ constructions of multilingualism and multilingual students reflect dominating language ideologies. We argue that a monolingual ideology (Blommaert 2009), a one-nation-one-language ideology (Blackledge & Creese 2010), purism (Ommeren 2017) and nativespeakerism (Ortega 2019) seem to work together in the teachers’ reflections and conceptions of multilingualism. A possible consequence of this may be that minority language students are held up against monolingual standards and end up failing because their competence in Norwegian will never reach the level that is expected.